A novel germline mutation in GP1BA gene N-terminal domain in monoallelic Bernard-Soulier syndrome. (17th November 2018) - Trizuljak, Jakub; Kozubík, Kateřina Staňo; Radová, Lenka; Pešová, Michaela; Pál, Karol; Réblová, Kamila; Stehlíková, Olga; Smejkal, Petr; Zavřelová, Jiřina; Pacejka, Milan; Mayer, Jiří; Pospíšilová, Šárka; et al.
Abstract: Mutations in the GP1BA gene have been associated with platelet-type von Willebrand disease and Bernard-Soulier syndrome. Here, we report a novel GP1BA mutation in a family with autosomal dominant macrothrombocytopenia and mild bleeding. We performed analyses of seven family members. Using whole-exome sequencing of germline DNA samples, we identified a heterozygous single-nucleotide change in GP1BA (exone2:c.176T>G), encoding a p.Leu59Arg substitution in the N-terminal domain, segregating with macrothrombocytopenia. This variant has not been previously reported. We also analysed the structure of the detected sequence variant in silico . In particular, we used the crystal structure of the human platelet receptor GP Ibα N-terminal domain. Replacement of aliphatic amino-acid Leu 59 with charged, polar and larger arginine probably disrupts the protein structure. An autosomal dominant mode of inheritance, a family history of mild bleeding episodes, aggregation pattern in affected individuals together with evidence of mutation occurring in part of the GP1BA gene encoding the leucine-rich repeat region suggest a novel variant causing monoallelic Bernard-Soulier syndrome.